ANALISIS PENDAPATAN PETANI TEBU DI DESA PAMOTAN KECAMATAN DAMPIT KABUPATEN MALANG - Rizal Anam Setiawan; Wahyu Hidayat; Hendra Kusuma (Program Studi Ekonomi Pembangunan, 2019)
ABSTRACTRevenue is the amount of income received by a resident on his performance during a given period, whether daily, weekly, monthly, or yearly. This study aimed to find out the factors that affect the income of cane farmers. The methods used are validity, reliability test, multiple linear regression tests, test classic assumptions test and hypothesis testing. The sampling technique using random sampling method formula. The samples use in this research is 75 respondents. The dependent variable in this research is the revenue of the cane farmer’s in Dampit and the independent variables include the labor, production cost, land area, and level education. The result of this research is that the labor, production cost and land area have significant and positive effect to income of public transportations drivers with a significant level 0,05 (5%). While variables include level of education have no significant.Keywords: income of cane farmers, labour, production cost, land area, andlevel of education